Water closets and water wastes in apartment buildin Water closets and water wastes in apartment buildings gs - Oliveira, Lúcia Helena de (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This paper presents water wastes indexes obtained from an investigation in outlets and water storage tanks of five apartment buildings in Goiânia. These indexes were gathered from theoretical studies and from a water consumption audit in buildings. The stages of the water audits and the methods used for leakage detection are also presented. The results indicate that high indexes of water leakage and loss were detected in water closet cisterns. It is highlighted that leaks in water closet cisterns can be the cause of approximately 30% of water waste in buildings.